Study on Blasting Technology for Open-Pit Layering of Complex Mine Adjacent to High and Steep Slope - Wang, Menglai; Li, Xiaoshaung; Li, Qihang; Hu, Yunjin; Chen, Qiusong; Jiang, Song (Frontiers in Earth Science, 2021)
In China, mining blasting vibration has seriously threatened the safety and stability of high and steep rock slopes. In this paper, taking the east mining area of Jianshan Phosphorus Mine as the research background, combined with field survey, field blasting test, numerical simulation and theoretical analysis, systematically studied the adjacent high-steep rock slope and the layered blasting technology of complex ore. Based on wide hole spacing blasting numerical simulation and field tests, the use of 8×4m hole network parameters, oblique line hole-by-hole initiation method, detonator delay using 35ms between holes, 65ms between rows and 500ms within the holes, the rock mass rate was reduced and the drilling workload was decreased. In addition, regression analysis was carried out on a large amount of vibration test data, and the attenuation law and propagation law of blasting vibration of adjacent high and steep slopes were predicted, which provided a reference for mine production blasting. By establishing a mathematical model of cumulative damage of rock mass blasting, it shows that the depth of impact of mining blasting on the slope of Jianshan open-pit was 0~3.6m, but the blasting did not cause overall damage to the adjacent high and steep slopes. In the future, this model can be used to predict rock damage caused by subsequent blasting.